Synergistic Activity of Dayak Onion and Halalang as Multi-Target Antidiabetic - Purnama, Shalvira (Pena Medika : Jurnal Kesehatan, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia due to impaired insulin secretion and/or action. The increasing global (approx. 589 million adults) and national (11.7% in Indonesia in 2023) prevalence highlights the critical need for effective therapies. This urgency drives the search for local alternatives like Eleutherine palmifolia (Dayak Onion) and Imperata cylindrica (Cogon Grass), traditionally used to control blood glucose. This review aims to examine their antidiabetic activity, identify multi-target mechanisms, and explore their potential synergy on insulin sensitivity. The method employed a narrative literature review of 23 scientific articles (2013–2025) sourced from PubMed, ScienceDirect, Google Scholar, and ResearchGate. Results show E. palmifolia lowers blood glucose and improves insulin resistance through pancreatic β-cell regeneration, α-glucosidase inhibition, and antioxidant activity. I. cylindrica reduces oxidative stress and enhances glucose utilization via anti-inflammatory mechanisms and improved mitochondrial function. In conclusion, the combination offers potential for a stronger synergistic effect in improving insulin sensitivity and blood glucose control. Recommendations include essential further testing through in vivo combination trials and toxicity tests to prove safety and effectiveness. Furthermore, in-depth exploration of molecular pathways (e.g., GLUT4, AMPK, insulin gene expression) is required to clarify the synergistic mechanism